Lack of association between matrix metalloproteinase-9 gene-1562C/T polymorphism and preeclampsia: a meta-analysis. (November 2014) - Gong, Li-Li; Liu, He; Liu, Li-Hong
<x xml:space="preserve">Abstract</x> Studies investigating the association between matrix metalloproteinases (MMPs) gene polymorphisms and preeclampsia (PE) reported contradictory or non-conclusive results. We performed a meta-analysis of five studies that examined the relationship between PE and the MMP9-1562C>T polymorphism. The PubMed, Embase, and Google Scholar databases were searched to access the relevant genetic association studies up to September 2013. The meta-analysis revealed that there was no evidence for significant association between MMP9-1562C>T polymorphism and risk of PE. Large, multiethnic confirmatory, and well-designed studies are needed to further explore the relation between preeclampsia and polymorphisms of the MMPs gene.